Pembuatan Aplikasi Poliklinik Universitas X Berbasis Web - Maria Alvinna; Kristo Radion Purba; Lily Puspa Dewi (Jurnal Infra, 2018)
Many health workers are not familiar with information technology in their service. Information technology in the health field can be patient record application, prescribing, until payment. However, the application is rarely used, especially in the Polyclinics of the University X who still do the recording manually. Thus, a web-based University of X Polyclinic application was created to replace manual logging. This application can facilitate the user in data processing, speed up the service process, as well as easier recording prescription. The Web aims to shorten prescription delivery from doctor to pharmacist, minimize prescription reading errors, and reduce paper usage. The basis for making this program is Laravel. Thus, with records performed by physicians and pharmacists at Polyclinic University X become more structured. At the time the patients come first queue up. The receptionist will perform patient data collection. The patient's data automatically goes to the intended doctor. Doctors enter the diagnosis and give medicine. The drug is automatically connected to the receptionist so it can be prepared. The sick letter, made by the doctor directly connected to the receptionist to be printed. From the results of system testing, can be taken some conclusions, namely the application can allow users to add, update, delete and in the output. speed up service process in Polyclinic University X, and facilitate user in doing recording doctor’s prescription.